Determination of Coaching Management of KONI Bogor Regency - Nurjaman, Ade (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to analyze the Determinants of Management Development of the Indonesian National Sports Committee (KONI) in Bogor Regency. The variables used are Planning, Organizing, Implementation, and Supervision as independent variables, and achievement as the dependent variable. The research method employs quantitative data obtained from questionnaires completed by 94 (Ninety-Four) athlete respondents who have achieved championships under the guidance of KONI Bogor Regency. The analysis was conducted using SPSS V.22 software. The results of the hypothesis testing analysis indicate that planning has a positive and significant effect on achievement. Organizing has a positive and significant effect on achievement. Implementation has a positive and significant effect on achievement. Supervision and evaluation also have a positive and significant effect on achievement. Furthermore, the combined influence of planning, organizing, implementation, supervision, and evaluation positively and significantly affects achievement. Keywords: Planning, Organizing, Implementation, Supervision, Achievement.